Pengaruh Kepuasan Pelanggan, Hambatan Beralih dan Kepercayaan Pelanggan Terhadap Retensi Pelanggan Pengguna Kartu Simpati Pada Mahasiswa Universitas Negeri Padang Rizki - Rizki Nanda; Susi Evanita; Whyosi Septrizola (Universitas Negeri Padang, 2019)
The purpose of this research is to analyze: (1) Effect of customer satisfaction on customer trust ofsimpati card users at Padang State University students, (2) Effect of switching barriers oncustomer trust of simpati card users at Padang State University students, and (3) Effect ofcustomer trust on customer retention of simpati card users at Padang State University students.A type of the research is causative. The study population was all students at Padang StateUniversity. The sampling technique used was purposive sampling. Total sample size of 100people. The data used are primary and secondary obtained by distributing questionnaires toselected students. The analytical methode used is descriptive and inductive through path analysis.The result showed that: (1) Customer satisfaction significant impact on customer trust of simpaticard users at Padang State University students, (2) Switching Barriers significant impact oncustomer trust of simpati card users at Padang State University students, (3) Customer trustsignificant impact on customer retention of simpati card users at Padang State University student,(4) Customer Satisfaction significant impact on customer retention of simpati card users atPadang State University student, and (5) Switching Barriers significant impact on customerretention of simpati card users at Padang State University student.Keywords: Customer Retention, Customer Satisfaction, Switching Barriers, and Customer Trust